2013
DOI: 10.2151/sola.2013-005
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Migration of the Baiu Frontal Zone over the East China Sea: Sea Surface Temperature Effect

Abstract: We propose a new scenario for the seasonal migration of the Baiu frontal zone over the East China Sea in which this migration is affected by variations in the sea surface temperature (SST). Using atmospheric and oceanic objective analysis datasets, a relationship was determined between the seasonal migration of the Baiu frontal zone and the decaying process of the cold high over the East China Sea. Before the middle of June, the cold high, cooled by the low SST, is present over the continental shelf, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The positive precipitation moves to the northern part of the Korean Peninsula or farther northward around late July (20-29 July) and becomes weaker thereafter. This northward migration of positive precipitation occurring in the Korean Peninsula from the middle of June to late July is related to the changma front and is an important characteristic of early summer precipitation in this region (Lee and Seo 2013;Moteki and Manda 2013).…”
Section: B Bcm Frontmentioning
confidence: 92%
“…The positive precipitation moves to the northern part of the Korean Peninsula or farther northward around late July (20-29 July) and becomes weaker thereafter. This northward migration of positive precipitation occurring in the Korean Peninsula from the middle of June to late July is related to the changma front and is an important characteristic of early summer precipitation in this region (Lee and Seo 2013;Moteki and Manda 2013).…”
Section: B Bcm Frontmentioning
confidence: 92%
“…Recent studies have pointed out the effects of SST variation in the ECS on the Baiu front. Moteki and Manda [2013] revealed a close relationship between seasonal migrations of the BFZ and SST on both climatological and synoptic timescales, suggesting the importance of surface heat fluxes over the ECS in seasonal migrations of the Baiu front. Kuwano-Yoshida et al [2013] demonstrated that surface evaporation over the warm ocean current was important for maintenance of the quasi-stationary BFZ.…”
Section: Introductionmentioning
confidence: 83%
“…Although the Baiu front is depicted as a stationary front on operational weather charts, the BFZ has strong variations in space and time [e.g., Ninomiya, 1984;Ninomiya and Akiyama, 1992;Ninomiya and Shibagaki, 2007;Moteki et al, 2004aMoteki et al, , 2004bMoteki et al, , 2006Maeda et al, 2008;Moteki and Manda, 2013]. The SST field in the northeastern ECS also exhibits large spatiotemporal variations.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A recent study further discussed an anchoring effect of the SST front on low‐level storm tracks and eddy‐driven polar front jets [ Ogawa et al ., ]. Several regional studies have also shown that the seawater temperature field strongly affects meteorological disturbances [e.g., Yamamoto and Hirose , ; Moteki and Manda , ]. The importance of the frontal SST gradient has also been demonstrated in many studies [e.g., Nonaka et al ., ; Sampe et al ., ].…”
Section: Introductionmentioning
confidence: 93%